Análise da influência da carga de hidrogenação na tenacidade à fratura quase estática de juntas soldadas dissimilares - Costa, Esdras Carvalho da (2018)
The present work analyzed the influence of hydrogen on the quasistatic toughness of welded joint dissimilar, consisting of AISI 8630M and ASTM A-36 steel base metals, with AWS ERNiCrMo-3 filler metal (commercially known as INCONEL 625). This joint, which is one of the most used in the oil industry, has presented brittle fractures in the ZTA regions, as a consequence of the metallurgical transformations and residual stresses caused by the thermal welding. The fracture toughness parameter used was the crack tip aperture displacement, known as Crack Tip Open Displecement (CTOD). Because it was a welded joint, the specimens used were of type SE (B), submitted to three-point bending and tested in the air after previous hydrogenation. The hydrogenation of CTOD specimens was performed in NaCl solution under loads of -650 mVSCE, -850 mVSCE and -1100 mVSCE. The electrochemical permeation tests used in the quantification of the retained hydrogen were performed in both the ZTA and the MB at two load levels of -650 mVSCE and -1100 mVSCE. In terms of the CTOD parameter, the results did not indicate the influence of the hydrogen in the welded joint embrittlement, analyzed in the three levels of established hydrogenation preloads. In turn, in terms of hydrogen permeation, there was an increase in the number of trapping sites of HAZ compared to MB.